2020
DOI: 10.31577/geogrcas.2020.72.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Faceted classification of the spring flood hydrographs of the Southern Buh river

Abstract: Faceted classification of the spring flood hydrographs of the Southern Buh river A hydrograph shape reflects the effect of hydrological, hydrobiological, hydromorphological, hydrochemical and other processes acting in river basins. Classification of river hydrographs could help to evaluate the long-term changes in river basins or compare hydrological response of different basins. We present the methodology of the spring flood hydrograph classification and show its application in the Southern Buh River basin, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The classification of hydrographs by similar shapes in them was carried out and it was shown that the presence of similar in shape hydrographs in the time series of classes indicates that from time to time the similar formation conditions of water flow at the catchment area repeats due to cyclicity of climatic and, as a consequence, of hydrological processes. In the study (Khrystiuk et al, 2020) the cyclicity of spring floods based on the classification of hydrographs by the facet method in the Southern Buh River Basin is showed.…”
Section: Results and Their Analysismentioning
confidence: 99%
“…The classification of hydrographs by similar shapes in them was carried out and it was shown that the presence of similar in shape hydrographs in the time series of classes indicates that from time to time the similar formation conditions of water flow at the catchment area repeats due to cyclicity of climatic and, as a consequence, of hydrological processes. In the study (Khrystiuk et al, 2020) the cyclicity of spring floods based on the classification of hydrographs by the facet method in the Southern Buh River Basin is showed.…”
Section: Results and Their Analysismentioning
confidence: 99%